Komunikasi Antarbudaya di kalangan Pedagang Kaki Lima : Studi Komunikasi Antarbudaya Pedagang Kaki Lima Yang Berbeda Etnis di depan Komplek MTQ Kota Pekanbaru - Niki Pratama; Tessa Shasrini (Prisani Cendekia Institute, 2023)
Abstract: This study aims to determine intercultural communication that occurs among street vendors which indirectly gives them an identity that communication is very important to adapt to a new environment which is called cultural adaptation. This research is a research that uses qualitative methods with a descriptive approach that helps share information. related to intercultural communication among street vendors of different ethnicities in front of the MTQ complex in Pekanbaru. The results show that intercultural communication that occurs among street vendors of different ethnicities in front of the MTQ complex in Pekanbaru city aims to interact between them street vendors of different ethnicities and for trading activities they. As well as the process of cultural adaptation by street vendors who have difficulty adapting to other traders of different ethnicities